Prediction of creep crack initiation behaviour in 316H stainless steel using stress dependent creep ductility - Quintero, Hanna; Mehmanparast, Ali (Elsevier, 2016)
The creep crack initiation behaviour of Type 316H stainless steel at 550 °C has been predicted by implementing a stress dependent creep ductility and average creep strain rate model in finite element analyses. Simulations were performed on five specimen geometries: C(T), CS(T), DEN(T), M(T) and SEN(T). The predicted results have been characterised using the C* fracture mechanics parameter and the short-term, long-term and transition creep crack initiation trends are predicted for each of the specimen geometries examined. The prediction results have been validated through comparison with experimental data available in the literature. The predicted short-term and long-term creep crack initiation trends have also been compared with NSW prediction lines. The predicted results, from each specimen geometry, are compared to each other and the differences in crack initiation trends have been discussed in terms of the specimen geometry, in-plane constraint and stress level effects on the creep crack initiation behaviour of the material. A mesh sensitivity analysis has also been performed to find the optimum mesh size for performing crack initiation simulations.
Keywords: Creep crack initiation; Constraint effects; Creep ductility; Specimen geometry; 316H stainless steel; Long term; Transition